Psychological profiles and quality of life differ between patients with dyssynergia and those with slow transit constipation - Rao, Satish S.C.; Seaton, Kara; Miller, Megan J.; Schulze, Konrad; Brown, C. Kice; Paulson, Jessica; Zimmerman, Bridget (Journal of psychosomatic research, 2007)
Pathophysiological characteristics differ between slow transit constipation (STC) and dyssynergic defecation, but whether psychological profiles and quality of life (QOL) are altered and whether they differ among these constipation subtypes are unknown. We prospectively evaluated psychological profiles and QOL in 76 patients with dyssynergia, 38 patients with STC, and 44 control subjects using the Revised 90-item Symptom Checklist and 36-item Short-Form Health Survey. In addition, we examined the correlations of psychological and QOL domains with constipation symptoms and pathophysiological subtypes. Symptom scores for hostility and paranoid ideation were higher ( P<.001) in patients with dyssynergic defecation than in patients with STC and control subjects. Scores for other psychological domains were higher ( P<.0001) in patients with dyssynergic defecation and those with STC than in control subjects. Most QOL subscores were impaired ( P<.05) in patients with dyssynergic defecation and some were impaired in patients with STC as compared with control subjects, but the two patient groups did not differ on these. The QOL subscores were strongly correlated ( r c≈.9) with the psychological subscores in patients with dyssynergic defecation and those with STC, although more QOL subscores among patients with dyssynergic defecation and more psychological subscores among patients with STC primarily contributed to the canonical correlations. A set of six commonly reported constipation symptoms showed significant correlations with QOL and psychological subscores, more so among patients with STC than among patients with dyssynergic defecation. Patients with dyssynergic defecation had greater psychological distress and impaired health-related QOL as compared with patients with STC and control subjects. Both patient groups were also more affected as compared with the control group. There was a strong correlation between psychological dysfunction and impaired QOL, and both also correlated with constipation symptoms.